Comparison of performance of radial, and upflow filters with conventional filters - Perera, Yahampath Arachchige Preethi; Vigneswaran, S.; Samorn Muttamara; Orth, H.M.; Royal Danish Government (Bangkok : Asian Institute of Technology, 1982)
The conventional method of designing rapid sand filters does not have a rational basis. It has long been known that a conventional filter did not use its entire filter bed in effective filtration. Most of the removal and head IOES took place at the top portion of the filter bed. This fact was observed from the extensive experiments in the present study. From the view point process kinetics, upflow and radial filters use their entire beds more efficiently in filtration action. The number of bed volumes t1ltered is the most meaningful basis for the comparison of performance to radial filters with that of upflow and conventional filters. It showed the advantages of upflow and radial tilters over conventional filters. IVES model developed for deep bed filters successfully explained the conventional filter performance. The attempt to simulate effluent concentrations of the radial filter produced satisfactory results; results of the conventional filter were taken as the the basis.
A thesis submitted in paSchool of Environment, Resources and Developmentrtial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1982
Keywords: Tanning -- Waste disposal